Design & characterization of timolol maleate Osmotic drug delivery system - B.Nagarani; A.Sravanthi; M.Santosh Kumar; R.Srikanth (International Journal of Pharmacy and Analytical Research, 2020)
The purpose of this study was to design and evaluate Push-Pull Osmotically Controlled Drug Delivery system of Timolol Maleate. Push pull osmotic tablets are bilayered tablets consisting of pull layer (drug layer) and push layer (polymer layer) coated with semi permeable membrane containing water leaching pore forming agents. Timolol Maleate is an oral antihypertensive agent which belongs to BCS class II drug with half life of 4 hours. Main objective to formulate this system was to achieve zero order release. The present study was also aimed to develop a system that would reduce the frequency of dosing and thus increases patient compliance. In this study an attempt was made to design formulations by using Stat-Ease design expert 9software. Opadry CA was used as film forming polymer. Sodium chloride was used as osmotic agents. This system was developed in two stages: (a) Formulation of core tablet & (b) coating of tablet core. Core tablets were evaluated for content uniformity, hardness, & weight variation while coated tablets were evaluated for film thickness and In Vitro release study. All the post compression and pre- compression parameters showed within limits. Selected formulation F2 having Polyox N-80 73.5% successfully retarded drug release for 24hrs and drug release follows Zero order kinetic with R2 value of 0.987. The Korsmeyer- Peppas equation showed the R2 value to be 0.918 and n value was 0.639 following Zero Order & Anomalous (Non- Fickian Diffusion).